A systematic review of occupationalradiation individual dose monitoring amonghealthcare workers exposed in Africa - Gbetchedji, Arnaud A; Houndetoungan, Gilles David; Hounsossou, Hubert C; Journy, Neige; Haddy, Nadia; Rubino, Carole; MEDENOU, Daton (My University, 2020)
Dosimetric monitoring is useful to limit exposures to ionising radiation in med-ical occupational settings, and reduce subsequent health risks. Scientific liter-atures, such as the UNSCEAR report 2017 and International Atomic EnergyAgency Report 2014b, updated information on this subject; however, fewAfrican works have been found. This is the reason why we undertook thisstudy, which summarises existing information on monitoring external radi-ation exposure doses for the whole body, using data from medical workerson this continent. Using standard terms and combining different keywordsearches for radiation dose monitoring among radiology healthcare workersin Africa, from the titles, abstracts, and full texts, we found 3139 articles inthe PubMed/MEDLINE, Google Scholar and INIS databases. Two reviewersscreened the retrieved publications based on predefined eligibility criteria toidentify relevant studies, extract key information from each, and summarisethe data in table form. A total of 20 potentially relevant articles were identi-fied. Among these 20 articles, 15 reported the overall average annual effective ose. Studies included in this systematic review represent an inventory of theradiation protection of medical workers in various African countries, with afocus on the monitoring of occupational radiation exposure. The size of stud-ied populations ranged between 81 and 5152 occupational exposed workers.The mean annual effective doses ranged from 0.44 to 8.20 mSv in all spe-cialities of medical sectors, while diagnostic radiology ranged from 0.07 to4.37 mSv. For the nuclear medicine and radiotherapy from medical groups, themean annual effective dose varied between 0.56 and 6.30 mSv. Industrial andresearch/teaching sectors data varied between 0.38 to 19.40 mSv. In conclu-sion, more studies implemented on dosimetric monitoring in Africa are neededto get a real picture of occupational exposure in the continent.
Keywords: healthcare workers; dose monitoring; occupational radiation exposure; diagnostic radiology; diagnostic x-ray; medical imaging; Africa